Transient and sustained increases in inositol 1,4,5-trisphosphate precede the differential growth response in gravistimulated maize pulvini - Perera, Imara Y. (The National Academy of Sciences, 1999)
The internodal maize pulvinus responds to gravistimulation with differential cell elongation on the lower side. As the site of both graviperception and response, the pulvinus is an ideal system to study how organisms sense changes in orientation. We observed a transient 5-fold increase in inositol 1,4,5-trisphosphate (IP(3)) within 10 s of gravistimulation in the lower half of the pulvinus, indicating that the positional change was sensed immediately. Over the first 30 min, rapid IP(3) fluctuations were observed between the upper and lower halves. Maize plants require a presentation time of between 2 and 4 h before the cells on the lower side of the pulvinus are committed to elongation. After 2 h of gravistimulation, the lower half consistently had higher IP(3,) and IP(3) levels on the lower side continued to increase up to ≈5-fold over basal levels before visible growth. As bending became visible after 8–10 h, IP(3) levels returned to basal values. Additionally, phosphatidylinositol 4-phosphate 5-kinase activity in the lower pulvinus half increased transiently within 10 min of gravistimulation, suggesting that the increased IP(3) production was accompanied by an up-regulation of phosphatidylinositol 4,5-bisphosphate biosynthesis. Neither IP(3) levels nor phosphatidylinositol 4-phosphate 5-kinase activity changed in pulvini halves from vertical control plants. Our data indicate the involvement of IP(3) and inositol phospholipids in both short- and long-term responses to gravistimulation. As a diffusible second messenger, IP(3) provides a mechanism to transmit and amplify the signal from the perceiving to the responding cells in the pulvinus, coordinating a synchronized growth response.